Quantitative Evaluation of Adult Subglottic Stenosis Using Intraoperative Long-range Optical Coherence Tomography. (October 2016) - Sharma, Giriraj K.; Chin Loy, Anthony; Su, Erica; Jing, Joe; Chen, Zhongping; Wong, Brian J-F.; Verma, Sunil
Objectives: To determine the feasibility of long-range optical coherence tomography (LR-OCT) as a tool to intraoperatively image and measure the subglottis and trachea during suspension microlaryngoscopy before and after endoscopic treatment of subglottic stenosis (SGS). Methods: Long-range optical coherence tomography of the adult subglottis and trachea was performed during suspension microlaryngoscopy before and after endoscopic treatment for SGS. The anteroposterior and transverse diameters, cross-sectional area (CSA), distance from the vocal cords, and length of the SGS were measured using a MATLAB software. Pre-intervention and postintervention airway dimensions were compared. Three-dimensional volumetric airway reconstructions were generated using medical image processing software (MIMICS). Results: Intraoperative LR-OCT imaging was performed in 3 patients undergoing endoscopic management of SGS. Statistically significant differences in mean anteroposterior diameter ( P < .01), transverse diameter ( P < .001), and CSA ( P < .001) were noted between pre-intervention and postintervention data. Three-dimensional airway models were viewed in cross-sectional format and via virtual "fly through" bronchoscopy. Conclusions: This is the first report of intraoperative LR-OCT of the subglottic and tracheal airway before and after surgical management of SGS in humans. Long-range optical coherence tomography offers a practical means to measure the dimensions of SGS and acquire objective data on the response to endoscopic treatment of SGS.